Educação, escola pública e autonomia - Sayão, Marcelo Nunes (1999)
The prime object of this work is the autonomy of public school. This has been, lately, one of the principal strategies of educational politics fonnulaters to promote changes in the teaching system. The relevancy of this theme being confrrmed nowadays, we begin our work placing the autonomy of public school in a historical context in which different political forces confront each other, thus giving configuration to a duel of educational directions that show up a whole vision of the world, of man and society. Starting from this historical context, we introduce the disputes about the autonomy concept, placing them in today's poli ti cal and economic moment of brazilian society. Finaly, in the last part of our work, we analyse one of the proposals for public school's autonomy that has been implemented by the Governrnent of the State of Rio de Janeiro between the years of 1995 and 1998.